2017
DOI: 10.1155/2017/5408503
|View full text |Cite
|
Sign up to set email alerts
|

An Automatic Tree Skeleton Extracting Method Based on Point Cloud of Terrestrial Laser Scanner

Abstract: Tree skeleton could describe the shape and topological structure of a tree, which are useful to forest researchers. Terrestrial laser scanner (TLS) can scan trees with high accuracy and speed to acquire the point cloud data, which could be used to extract tree skeletons. An adaptive extracting method of tree skeleton based on the point cloud data of TLS was proposed in this paper. The point cloud data were segmented by artificial filtration and -means clustering, and the point cloud data of trunk and branches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Furthermore, they developed an open source tool named Simple Tree to provide an efficient optimization approach for tree reconstruction [73]. Recently, Li et al [74] proposed an adaptive extracting method of tree skeleton based on the point cloud data with a terrestrial laser scanner, and obtained consistent tree structure. A Lidar sensor also has been tried for the branch length and diameter identification [75].…”
Section: Lidar Based Machine Vision Systemmentioning
confidence: 99%
“…Furthermore, they developed an open source tool named Simple Tree to provide an efficient optimization approach for tree reconstruction [73]. Recently, Li et al [74] proposed an adaptive extracting method of tree skeleton based on the point cloud data with a terrestrial laser scanner, and obtained consistent tree structure. A Lidar sensor also has been tried for the branch length and diameter identification [75].…”
Section: Lidar Based Machine Vision Systemmentioning
confidence: 99%
“…The next step is to quantify tree semantics from the isolated point cloud data (Pfeifer et al, 2004, Livny et al, 2010, Leavenworth, 2012 by segregating the tree point clouds into the above-ground woody structures and the tree crown. At present, we are not aware of any commercial software for this segregation step, although some relevant techniques have been demonstrated (Bland et al, 2014).Works such as (Li et al, 2017) use the intensity information found in typical point cloud data to differentiate the woody structure (trunk) and crown (leaves). Other works (Xu et al, 2007a, Wang et al, 2014 use minimum spanning tree construction based on neighbours' distances to construct tree skeletons.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lidar sensor/ToF sensor 3D sensing (Stereo camera; Kinect; 3D camera) RGB/RGBD cameras Medeiros et al (2017); Chattopahdyay et at., Karkee et al, 2014Tabb et al, 2018;Elfiky et al, 2015Akbar et al, 2016aAkbar et al, 2016b Lidar based machine vision systems have been mainly used for biomass mapping or individual tree detection, especially for the forest application (Brandtberg et al, 2003;Edson and Wing, 2011;Van Aardt et al, 2008). Recently, Li et al (2017) proposed an adaptive extracting method of tree skeleton based on the point cloud data with a terrestrial laser scanner, and obtained consistent tree structure. A Lidar sensor also has been tried for the branch length and diameter identification (Bucksch and Fleck, 2011).…”
Section: Machine Vision Sensing For Branch Detection and Identificationmentioning
confidence: 99%